EFFECT OF FIBER VOLUME ON ELASTIC MODULUS OF POST-CORE FABRICATED REINFORCED COMPOSITE - Benyamin, Benni; Ekoningtyas, Endah Aryati; Christiono, Sandy; Fatmawati, Dwi Warna Ayu (Odonto : Dental Journal, 2023)
Background: Post-core restoration is one restoration after endodontic treatment by optimizing the root canal as a retention. Fracture of the root is the most common failure due to the post being less elastic in holding the chewing load, especially the metal post. FRC post-core indicates to prevent tooth fracture. In addition, the FRC post-core minimizes the reduction of dentine tissue in the root canals, called a minimally invasive dentistry approach. This study examined the effect of the number of fibres on the elastic moduli of fabricated FRC posts using a three-bending point test to determine the elasticity of fabricated FRC posts. Method: The study was experimental laboratory research with the post-only control group design using polyethene fibre (Kerr) and flowable composite resin (Kerr), prefabricated post-core (Kerr). The study was divided into four groups, namely prefabricated, fabricated with a volume of 1 fibre, 2 fibres, and 3 fibres, where each group consisted of 6 samples. Result: There was no significant difference in the magnitude of the force on the specimen (p>0.05). The force among the groups was the same, the alteration (deflection) of the specimens among the groups was significantly different (p